Blackcurrant press cake by-product: increased chemical bioaccessibility and reduced antioxidant protection after in vitro simulation of gastrointestinal digestion - dos Santos Lima, Amanda; Maltarollo, Vinicius G.; Araújo Vieira do Carmo, Mariana; Cezar Pinheiro, Lucas; Mendanha Cruz, Thiago; Augusto Ribeiro de Barros, Frederico; Pap, Nora; Granato, Daniel; Azevedo, Luciana (Elsevier, 2024)
This study describes the bioaccessibility in terms of total phenolic content (TPC) and antioxidant capacity before and after in vitro digestion from blackcurrant press cake extracts (BPC) and the bioactivity in cell culture, human erythrocytes as well as the in silico analysis. Chemical analysis of BPC presented an increase in TPC (270%) and anthocyanins (136%) after in vitro digestion, resulting in an improvement of antioxidant activity (DPPH 112%; FRAP: 153%). This behavior may be related to the highest activity of cyanidin-3-rutinoside, as confirmed by in silico analysis. The digested BPC did not exert cytotoxicity in cells and showed less antioxidant activity against the oxidative damage induced in endothelial cells and human erythrocytes compared to the non-digested extract. The results raise a question about the reliability we should place on results obtained only from crude samples, especially those that will be used to produce foods or nutraceuticals.
Keywords: anthocyanins; digestion; erythrocytes; phenolic compounds; by-products; oxidative stress